The Role of Autophagy in Breast Cancer Metastasis - Hye Min Kim; Ja Seung Koo (Biomedicines, 2023)
Patient morbidity and mortality is significantly increased in metastatic breast cancer. The metastasis process of breast cancer is very complicated and is delicately controlled by various factors. Autophagy is one of the important regulatory factors affecting metastasis in breast cancer by engaging in cell mobility, metabolic adaptation, tumor dormancy, and cancer stem cells. Here, we discuss the effects of autophagy on metastasis in breast cancer and assess the potential use of autophagy modulators for metastasis treatment.